2018
DOI: 10.2334/josnusd.17-0221
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implant clinical and radiographic status and whole salivary cotinine levels among cigarette and waterpipe smokers and never-smokers

Abstract: The aim was to compare the peri-implantclinical and radiographic inflammatory parameters and whole salivary cotinine levels among cigarette smokers (CS), waterpipe smokers (WS) and neversmokers (NS). Thirty-four CS (Group 1), 33 WS (Group 2), and 31 NS (Group 3) were included. Peri-implant plaque index (PI), bleeding-on-probing (BOP), and probing depth (PD) were measured, and crestal bone loss (CBL) was assessed on standardized digital radiographs. Unstimulated whole saliva samples were collected and whole sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…According to Adil and colleagues complications in bone mineral metabolism are often occasionally observed in patients with chronic hyperglycemia compared with individuals without diabetic status. Similarly, PBL around implants has been reported among tobacco‐smokers compared with healthy nonsmoking controls . We, therefore, speculate that tissue inflammation and PBL are significantly higher around NDIs placed in diabetic patients and tobacco‐smokers compared with systemically healthy never‐smokers.…”
Section: Discussionsupporting
confidence: 53%
“…According to Adil and colleagues complications in bone mineral metabolism are often occasionally observed in patients with chronic hyperglycemia compared with individuals without diabetic status. Similarly, PBL around implants has been reported among tobacco‐smokers compared with healthy nonsmoking controls . We, therefore, speculate that tissue inflammation and PBL are significantly higher around NDIs placed in diabetic patients and tobacco‐smokers compared with systemically healthy never‐smokers.…”
Section: Discussionsupporting
confidence: 53%
“…It is pertinent to mention that increased tobacco smoking increases the serum levels of cotinine and advanced glycation end products (AGEs) and their receptors (RAGEs), which in turn augment the levels of destructive proinflammatory cytokines, such as interleukins and tumor necrosis factor alpha (TNF‐α) . Higher levels of these biomarkers in the oral fluids is associated with the pathogenesis of inflammatory periodontal and periimplant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] During waterpipe smoking, charcoal-heated air passes through flavored tobacco and bubbles through water before inhalation. [11][12][13] During waterpipe smoking, charcoal-heated air passes through flavored tobacco and bubbles through water before inhalation.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] During waterpipe smoking, charcoal-heated air passes through flavored tobacco and bubbles through water before inhalation. Studies 12,13 have shown that periimplant probing depth (PD), plaque index (PI), and CBL are significantly high in waterpipe smokers compared with nonsmokers. The electric current heats up the e-liquid that converts into a vapor that is inhaled in a manner like conventional tobacco smoking.…”
Section: Introductionmentioning
confidence: 99%